Optimization Formula of Turmeric (Curcuma longa L.) Extract Chewable with Combination of Mannitol-Lactose as Filler Based on Simplex Lattice Design - Dian Eka Ermawati; Saifullah Sulaiman; Indah Purwantini (Universitas Sebelas Maret, 2017)
Hydroalcoholic extract of turmeric (Curcuma longa L.) doses of 1.66 mg/kg containing 10% of curcuminoid was recommended as a supplement for prevention of atherosclerosis. This study aimed to formulate hydroalcoholic extract of turmeric into chewable which are more acceptable and practical. Mannitol-Lactose selected as a filler to make the chewable in this study. Optimum composition of filler of the mixture obtained by the Simplex Lattice Design method.Identification of turmeric rhizome has been done at Departemen of Plant Taxonomy, Faculty of Biology, Gadjah Mada University, Yogyakarta, Indonesia. The rhizome extraction carried out as re to research carried out by Quiles. The mixture between curcuminoid, ethanol and water extract made up to 25% level of curcuminoid level. Then, Extract was granulated with combination of filler mannitol-lactose to be five formulas, there are: FI (mannitol 100%), FII (mannitol-lactose 75%:25%), FIII (mannitol-lactose 50%:50%), FIV (mannitol-lactose 25%:75%), FV (lactose 100%). The granules then tested their physical properties such as flowability, compactibility, and water content. Furthermore, the granules tableted and physical tested including : weight uniformity, hardness, friability, absorption, flavor acceptance and soluble time. Determining the optimum formulation obtained from the physical properties of the granules and chewable physical properties based on SLD methods. Optimum formula of chewable then tested with kurkuminoid levels. The physical properties data of granules and chewable were analyzed statistically using student’s t-test.The result of this study was the optimum formula obtained from the mixture of mannitol-lactose fillers with a ratio of 90% mannitol: 10% lactose. The optimum formula of turmeric extract chewable produced meets the physical properties of the granules and chewable. Acceptance of flavor chewable optimum formula appreciation in the range of sweet and sour taste to sour. Percentage kurkuminoid levels in chewable after manufacture process was 76.42%.